Democratic Deficits in Europe: The Overlooked Exclusiveness of Nation‐States and the Positive Role of the European Union*. (28th October 2016) - Blatter, Joachim; Schmid, Samuel D.; Blättler, Andrea C.
Abstract: With the help of the Immigrant Inclusion Index (IMIX), a quantitative tool for measuring the electoral inclusion of immigrants, we demonstrate that European democracies are much more exclusive than they should be. All normative theories of democracy share the conviction that it is imperative that democracies include long‐term immigrant residents into the demos – either by granting citizenship or by introducing alien voting rights. But even the 20 most established and stable democracies within the EU are far from fully realizing the ideal of 'universal suffrage'. This is true independently of whether we count in‐ and excluded people in numerical terms, or whether we evaluate the relevant laws and regulations. Therefore, we diagnose a substantial democratic deficit on the level of European nation‐states. By requiring its member states to enfranchise non‐national EU citizens on the local level, the EU, for once, plays a positive role in reducing one of the most fundamental democratic deficits in times of migration.